EFFECTIVENESS ANALYSIS OF LIQUID ORGANIC FERTILIZER MADE FROM CATFISH (Clarias sp.) VISCERA WASTE ON THE PRODUCTIVITY OF Azolla microphylla - Andika Hasyim; Ni Nyoman Dian Martini; Jasmine Masyitha Amelia (Aquasains: Jurnal Ilmu Perikanan dan Sumberdaya Perairan, 2026)
Catfish (Clarias sp.) viscera waste has the potential to pollute the environment but contains high levels of N, P, and K nutrients. This study aimed to determine the effect of liquid organic fertilizer (LOF) made from catfish viscera waste on the productivity of Azolla microphylla and to identify the most effective dosage. A Completely Randomized Design (CRD) with three treatments was used: P0 (control, no LOF), P1 (dose 2.250 ml/L), and P2 (dose 2.625 ml/L), each replicated three times. LOF was produced through 14-day fermentation using Lactobacillus spp. probiotic. Azolla microphylla was cultivated in 25-liter buckets with an initial weight of 30 g for 30 days. Parameters measured included absolute weight growth and daily growth rate. ANOVA results showed significant differences among treatments (p=0.009). Tukey Post Hoc test indicated that P1 and P2 differed significantly from P0 but not from each other. Treatment P1 produced the highest absolute weight growth (203.00 g), followed by P2 (173.33 g) and P0 (108.67 g). A dose of 2.250 ml/L was the most effective dosage to enhance Azolla microphylla productivity.